Management of a Large Congenital Hemangioma Obstructing Visual Axis: A Case Report and Review of Literature. Issue 6 (November 2019) - AlShaker, Sara; Jivraj, Imran; Chen, Haiying; Muthusami, Prakash; Phillips, John; DeAngelis, Dan
Abstract : Congenital hemangiomas comprise a subset of vascular tumors with clinicopathologic features that are distinct from the more common infantile hemangioma. The authors present a patient with a large congenital hemangioma involving the forehead and brow which obstructed the visual axis and created significant risk for deprivational amblyopia. Management of the congenital hemangioma involved customized headgear to clear the visual axis and early vascular embolization of feeder vessels with the subsequent successful surgical resection at 23 days of life. A large amblyogenic congenital hemangioma required a multidisciplinary approach involving early vascular embolization of feeder vessels and subsequent surgical resection at 23 days of life.